2001
DOI: 10.1067/mhn.2001.116779
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Sinus Symptoms and Correlation with Paranasal Computed Tomography Scan

Abstract: The certainty of a clinical diagnosis of rhinosinusitis requiring treatment is enhanced in patients with high symptom severity scores for fatigue, sleep disturbance, nasal discharge, nasal blockage, or decreased sense of smell. Isolated headache and facial pain or pressure are less reliable predictors of CT scan findings supporting the diagnosis rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 11 publications
12
98
4
1
Order By: Relevance
“…91,108 Interestingly, sleep disturbance, fatigue, nasal blockage, and nasal discharge were more reliable predictors of a rhinosinusitis diagnosis (confirmed by computed tomography scan) than were headache or facial pain or pressure. 109 Most patients with symptoms of acute rhinosinusitis are treated with antibiotics; however, the viral nature of most rhinosinusitis infections suggest that antibiotics may be overused. 110,111 Patients with chronic rhinosinusitis, and chronic rhinosinusitis with nasal polyposis, commonly present with nasal obstruction, nasal discharge, facial pressure, pain, and hyposmia of prolonged duration.…”
Section: Acute Rhinosinusitis and Nasal Polyposis: Association With Amentioning
confidence: 99%
“…91,108 Interestingly, sleep disturbance, fatigue, nasal blockage, and nasal discharge were more reliable predictors of a rhinosinusitis diagnosis (confirmed by computed tomography scan) than were headache or facial pain or pressure. 109 Most patients with symptoms of acute rhinosinusitis are treated with antibiotics; however, the viral nature of most rhinosinusitis infections suggest that antibiotics may be overused. 110,111 Patients with chronic rhinosinusitis, and chronic rhinosinusitis with nasal polyposis, commonly present with nasal obstruction, nasal discharge, facial pressure, pain, and hyposmia of prolonged duration.…”
Section: Acute Rhinosinusitis and Nasal Polyposis: Association With Amentioning
confidence: 99%
“…The American Academy of Otolaryngology has recommended the Lund and Mackay system for CT staging of CRS [18]. The choice of CRS therapy depends upon symptom intensity and includes topical steroids, antibiotics and/or surgery [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Although publications on the correlation of symptoms of CRS to CT findings exist in the literature, similar works using plain radiographs of the PNS are not as numerous. [26][27][28] Da Lilly-Tariah et al in a similar study concluded that plain radiographs were useful in the diagnosis of chronic diseases of the paranasal sinuses while Kolo et al working in the northern part of Nigeria found the usefulness of plain sinus radiographs in the diagnosis of CRS questionable. 25,29 He also reported a weak insignificant correlation between symptom severity scores and findings on plain radiographs of the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%